Which AGN jets quench star formation in massive galaxies?. Issue 1 (19th July 2021) - Su, Kung-Yi; Hopkins, Philip F; Bryan, Greg L; Somerville, Rachel S; Hayward, Christopher C; Anglés-Alcázar, Daniel; Faucher-Giguère, Claude-André; Wellons, Sarah; Stern, Jonathan; Terrazas, Bryan A; Chan, T K; Orr, Matthew E; et al.
ABSTRACT: Without additional heating, radiative cooling of the halo gas of massive galaxies (Milky Way-mass and above) produces cold gas or stars exceeding that observed. Heating from active galactic nucleus (AGN) jets is likely required, but the jet properties remain unclear. This is particularly challenging for galaxy simulations, where the resolution is orders-of-magnitude insufficient to resolve jet formation and evolution. On such scales, the uncertain parameters include the jet energy form [kinetic, thermal, cosmic ray (CR)]; energy, momentum, and mass flux; magnetic fields; opening angle; precession; and duty cycle. We investigate these parameters in a $10^{14}\, {\rm M}_{\odot }$ halo using high-resolution non-cosmological magnetohydrodynamic simulations with the FIRE-2 (Feedback In Realistic Environments) stellar feedback model, conduction, and viscosity. We explore which scenarios qualitatively meet observational constraints on the halo gas and show that CR-dominated jets most efficiently quench the galaxy by providing CR pressure support and modifying the thermal instability. Mildly relativistic (∼MeV or ∼10 10 K) thermal plasma jets work but require ∼10 times larger energy input. For fixed energy flux, jets with higher specific energy (longer cooling times) quench more effectively. For this halo mass, kinetic jets are inefficient at quenching unless they have wide opening or precession angles. Magnetic fields also matter less except when the magnetic energy flux reaches ≳ 10 44 erg s −1 in a kinetic jet model, which significantly widens the jet cocoon. The criteria for a successful jet model are an optimal energy flux and a sufficiently wide jet cocoon with a long enough cooling time at the cooling radius.